Dampak Analisis Media Sosial oleh Eksekutif Penjualan terhadap Proses Pengambilan Keputusan Pembelian Pelanggan di PT Nasmoco Bahtera Motor - Affandi, Azhar; Setyaning, Aldilla Nadhira Ayu (Universitas Hamzanwadi, 2025)
This study examines the challenges faced by PT Nasmoco Bahtera Motor in utilizing social media as part of their digital marketing strategy. In an era where social media is crucial for building customer relationships and enhancing sales, many sales personnel lack the necessary understanding and skills for effective use. The aim of this research is to analyze the strategies employed by sales executives in leveraging social media for branding and to identify the obstacles they encounter. With appropriate training, sales personnel can become more effective in reaching customers and fostering loyalty towards the Toyota brand. This research uses surveys and interviews to gather data from sales personnel, providing insights into best practices and challenges in social media use. The findings are expected to offer practical recommendations for the company to formulate more effective digital marketing strategies, thereby increasing brand awareness and strengthening customer relationships in a competitive market.